Development of Learning Media for Pencak Silat Materials Based on Articulate Storyline for Grade VI Students at SDN Sukorejo I - Siswanto, Mamluatuz Zahirah; Kurniawan, Ari Wibowo (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2025)
Articulate Storyline is an application with numerous features, designed to facilitate students' understanding of pencak silat material. The purpose of this study was to develop learning media for pencak silat material based on an articulate storyline for grade VI students of SDN Sukorejo 1. The Research and Development method with the ADDIE model was used in this study by: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The samples involved in this study consisted of 30 grade VI students from SDN Sukorejo I and the PJOK teacher of SDN Sukorejo I. Additionally, several experts contributed to this study. Additionally, several experts contributed to this research. Additionally, several experts were involved in product validation, including a media expert, a material expert, and a physical education learning expert. The instruments used in this research are interview guidelines, product assessment questionnaires, and documentation. This articulate storyline learning media obtained 97% from the Media Expert with very valid criteria, obtained 96% from the Material Expert with very valid criteria, obtained 98% from the Learning Expert with very valid criteria, the PJOK Teacher SDN Sukorejo I test obtained 99%, and the field test obtained 88% with very valid criteria. Based on these results, this approach is feasible for use in the learning process.